Development of a Checklist to Prevent Reconstructive Errors Made By Undergraduate Dental Students. Issue 7 (27th April 2020) - Almufleh, Balqees; Ducret, Maxime; Malixi, Jodeci; Myers, Jeffrey; Nader, Samer Abi; Franco Echevarria, Maria; Adamczyk, Jessica; Chisholm, Alicia; Pollock, Natalie; Emami, Elham; Tamimi, Faleh
Abstract: Purpose: To design a checklist in order to reduce the frequency of reconstructive preventable errors (PE) performed by undergraduate dental students at McGill University. Materials and Methods: The most common PE occurring at a university dental clinic were identified by three reviewers analyzing the refunded cases, and used to create a preliminary checklist. This checklist was then validated by a panel of dental educators to produce a finalized 20‐item checklist. The 20‐question checklist was then submitted to students in a cross‐sectional survey‐based study to evaluate its relevance to undergraduate clinical education needs. Results: As many as 81% of students reported to have forgotten at least one item of the checklist during care of their last patient, and the most forgotten checklist items corresponded to the pretreatment stage. The students also reported that 17 of the 20 items in the checklist were relevant to a considerable extent or highly relevant. Conclusion: Common PE identified in the undergraduate clinic could be used to create a checklist of relevant items designed to reduce errors made by students and practitioners performing prosthodontic and reconstructive treatments. However, further studies are required to evaluate the implementation and efficiency of the checklist.